2006
DOI: 10.1186/1471-2296-7-9
|View full text |Cite
|
Sign up to set email alerts
|

Older adults' beliefs about physician-estimated life expectancy: a cross-sectional survey

Abstract: Background: Estimates of life expectancy assist physicians and patients in medical decisionmaking. The time-delayed benefits for many medical treatments make an older adult's life expectancy estimate particularly important for physicians. The purpose of this study is to assess older adults' beliefs about physician-estimated life expectancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 30 publications
2
42
0
Order By: Relevance
“…Estimates of HALE by urologists and radiation oncologists [3] as well as by primary care providers [24] also had a high margin of error. In one study, 64% of patients felt that their physicians were “unskilled, ill-equipped, and uncomfortable with the task” of estimating HALE [24].…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of HALE by urologists and radiation oncologists [3] as well as by primary care providers [24] also had a high margin of error. In one study, 64% of patients felt that their physicians were “unskilled, ill-equipped, and uncomfortable with the task” of estimating HALE [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, older adults' life expectancy varies depending upon age and health status. Inaccuracies with estimating life expectancy are well described [7] and it is unclear whether physicians or patients take life expectancy into account when making medical decisions [8].…”
Section: Introductionmentioning
confidence: 99%
“…A theoretical model was developed that describes the process of decision making by caregivers of family members with HF (see Figure 1). Triangulation is a method used by qualitative researchers to establish validity in their work (Guion, 2002). Theory triangulation involves the use of multiple theoretical perspectives to draw inferences or conclusions from a set of data in an effort to validate data findings (Watson, McKenna, Cowman, & Keady, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, not all caregivers and patients want information regarding the prognosis of the illness. Fried, Bradley, and O'Leary (2003) studied end-of-life care in cancer patients and found that many elders and caregivers are unable or unwilling to accept a prognosis of limited life expectancy despite previous reports indicating a desire for such disclosure. Hansen, Archbold, Stewart, Westfall, and Ganzini (2005) report that role strain for caregivers exists during the actual decision-making phase, as well as during the days, months, and years prior to the event and may continue after the decisions are made.…”
Section: Decision Making In Caregivingmentioning
confidence: 97%